Neuroprotective Effects of Asparagus officinalis Stem Extract in Transgenic Mice Overexpressing Amyloid Precursor Protein. (10th May 2021) - Peng, Zhanglong; Bedi, Supinder; Mann, Vivek; Sundaresan, Alamelu; Homma, Kohei; Gaskey, Gregory; Kowada, Minoru; Umar, Shahid; Kulkarni, Anil D.; Eltzschig, Holger K.; Doursout, Marie-Francoise
Abstract : To mimic Alzheimer's disease, transgenic mice overexpressing the amyloid precursor protein (APP) were used in this study. We hypothesize that the neuroprotective effects of ETAS®50, a standardized extract of Asparagus officinalis stem produced by Amino Up Co., Ltd. (Sapporo, Japan), are linked to the inhibition of the apoptosis cascade through an enhancement of the stress-response proteins: heat shock proteins (HSPs). APP-overexpressing mice (double-transgenic APP and PS1 mouse strains with a 129s6 background), ages 6-8 weeks old, and weighing 20-24 grams were successfully bred in our laboratory. The animals were divided into 5 groups. APP-overexpressing mice and wild-type (WT) mice were pretreated with ETAS®50 powder (50% elemental ETAS and 50% destrin) at 200 mg/kg and 1000 mg/kg body weight. Saline, the vehicle for ETAS®50, was administered in APP-overexpressing mice and WT mice. ETAS®50 and saline were administered by gavage daily for 1 month. Cognitive assessments, using the Morris Water Maze, demonstrated that memory was recovered following ETAS®50 treatment as compared to nontreated APP mice. At euthanization, the brain was removed and HSPs, amyloid β, tau proteins, and caspase-3 were evaluated through immunofluorescence staining with the appropriate antibodies. Our data indicate that APP mice have cognitive impairment along with elevated amyloid β, tau proteins, and caspase-3. ETAS®50 restored cognitive function in these transgenic mice, increased both HSP70 and HSP27, and attenuated pathogenic level of amyloid β, tau proteins, and caspsase-3 leading to neuroprotection. Our results were confirmed with a significant increase in HSP70 gene expression in the hippocampus.